Determinação do tamanho da amostra para avaliação de híbridos de melão amarelo - Moura, Kallyo Halyson Santos (2008)
The sample size in experiments should be determined so that it can accurately estimate the parameters of interest and to save time, labor and resources. The objective of the present work was to determine the sample size in evaluation experiments of melon hybrids in Mossoró. An experiment was carried out in randomized blocks with three replications to evaluate twenty yellow melon hybrids. The experimental plot consisted of two rows of 5.0 m with twenty plants in the spacing of 2.0 x 0.5 m. The traits evaluated were pulp thickness and firmness, content of soluble solids and fruit mean weight. Data were taken plant to plant, identifying each one harvested fruits. The methods used were of bootstrap resampling, linear model in plateau, sampling ntensity and modified maximum curvature to determine the sample size. The sample size recommended to determining for pulp thickness, fruit mean weight, content of soluble solidsand pulp firmness is 13, 13, 9 and 8 fruits, respectively. The Minimum sample size determined by modified maximum curvature method to pulp thickness, fruit mean weight, content of soluble solids and pulp firmness were 6,32; 7,35; 5,32and 3,25, respectively